PENERAPAN MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SDN 22 SUNGAI PAKNING - Nurmiati, Nurmiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
Classroom Action Research (CAR) aims to improve learning outcomes in grade VI SDN 22 Sungai Pakning. On the basis of the necessary application of the cooperative model STAD type to be able to assist students in improving their knowledge. Use of cooperative model STAD type of learning is expected to improve students' skills in science teaching in turn is expected to increase learning outcomes are achieved. After the action, then monitored, and the data collected, further processed and analyzed, the obtained result is the average percentage of mastery learning students ranging from pre cycle=41,00%, the first cycle=62,50%, and the second cycle=91,66%. Based on the above, it can be concluded that the cooperative model type STAD effect on improving student learning outcomes.Key words : cooperative model, learning outcomes